The African trilogy Things fall apart ; No longer at ease ; Arrow of God - Achebe, Chinua (New York Alfred A. Knopf, 2010)
Here, collected for the first time in Everyman?s Library, are the three internationally acclaimed classic novels that comprise what has come to be known as Chinua Achebe?s ?African Trilogy.?
Keywords: Igbo (African people) Fiction